Transcriptional regulation of the vascular endothelial glycome by angiogenic and inflammatory signalling - Willhauck-Fleckenstein, Martina; Möhler, Thomas; Merling, Anette; Pusunc, Susann; Goldschmidt, Hartmut; Schwartz-Albiez, Reinhard (Angiogenesis, 2010)
Vascular endothelial cells undergo many molecular changes during pathological processes such as inflammation and tumour development. Tumours such as malignant lymphomas affecting bone marrow are dependent on interactions with endothelial cells for (1) site-specific homing and (2) tumour-induced angiogenesis. Modifications in glycosylation are responsible for fine-tuning of distinct endothelial surface receptors. In order to gain a comprehensive insight into the regulation of the endothelial glycome, comprising genes encoding for sugar transporters (sugar s/t), glycosyltransferases (GT), glycan-degrading enzymes (GD) and lectins (GBP), we performed gene profiling analysis of the human bone marrow-derived microvascular endothelial cell line HBMEC-60 that resembles closely in its biological behaviour primary bone marrow endothelial cells. HBMEC were activated by either angiogenic VEGF or the inflammatory cytokine TNF. Approximately 48% (207 genes) of the 432 glycome genes tested were found to be expressed in HBMEC-60 cells. Inflammatory and angiogenic signals produce different profiles of up- or down-regulated glycome genes, most prominent changes were seen under TNF stimulation in terms of signal intensity and number of alterations. Stimulation by VEGF and TNF affected primarily genes encoding for glycosyltransferases and in particular those important for terminal modulation. For instance, an enhanced α2,6 sialylation was observed after TNF stimulation at the transcriptional and glycan expression level whereas transcription of ST3Gal1 sialylating in α2,3 position was enhanced after VEGF stimulation. Transcriptional analysis of the glycome gives insights into the differential regulation of glycosylation pathways and may help to understand the functional impact of endothelial glycosylation.
Gesehen am 07.01.2022